The Simulation of a Large-Scale Military Activity - Geisler, Murray A. (Management Science, 1959)
This paper was originally given at the Fifth International Meeting of the Institute of Management Sciences. It describes the first experiment of the RAND Logistics Systems Laboratory, which was concerned with testing a series of logistics policies in a detailed man-machine simulation. The paper describes the policies, the elements simulated, the operation of the experiment, and its results. It also briefly mentions the second or current experiment of the Laboratory.